Fuzzy modelling for burst pressure strength in radial friction welding of GI pipes. (20th July 2009) - Singh, Jagdev; Gill, Simranpreet Singh
The service of the welded tubular joints of circular pipes that are used to transfer fluid at high pressures is generally evaluated on the basis of their ability to endure the high pressures of the flowing fluid. In this paper, a practical and consistent fuzzy logic based model is presented to predict the burst pressure strength of tubular joints of GI pipes that are welded with the technique of friction welding. The model is based on two input signals: rotational speed and forge load. The adaptive neuro-fuzzy inference system (ANFIS) technique of fuzzy-based systems for modelling and simulation of the complex systems has been employed, which combined modelling function of fuzzy inference with the learning ability of artificial neural network. The set of rules has been generated directly from the experimental data using ANFIS. The performance of the model is validated by comparing the predicted results with the actual practical results obtained by conducting the confirmation experiments. The proposed model can be used for intelligent online adaptive control mode.